Recent advances in facial soft biometrics - Arigbabu O.A.; Ahmad S.M.S.; Adnan W.A.W.; Yussof S. (Springer Verlag, 2023)
Biometrics; Feature extraction; Image retrieval; Semantics; Controlled environment; Descriptors; Face recognition systems; Feature extraction methods; Realistic scenario; Scientific researches; Soft biometrics; State-of-the-art techniques; Face recognition